Recepção crítica de ''A hora da estrela'' : uma celebração ao centenário de Clarice Lispector - SOUSA, Eliene Rodrigues (Università di Bologna, 2022)
This work intends to present and discuss the critique on The hour of the star(1977), (re)evaluating the importance of the novel as Lispector’s legacy. Critical review on academic and media texts referring to the novel is used here. Results: Brazilian media posits the narrative in terms of explicitation vs. introspection, social engagement and aesthetic sublimation; foreign columnists discuss the readability of the novel and its place among great works; academic critique indicates that the novel contests patterns, subverting logic, the idea of narrative completion and authoritarian views.